School administration and supervision - Gregorio, Herman C. (Quezon City, 1961)
The many changes in educational thought and practice in the past few years had considerable effect on school administration and supervision. The increasing size of the educational enterprise and the broadening concepts of the role of leadership are a few of the forces which are evolving. a newer definition of the administrative and' supervisory functions, and a re-evaluation of the role of the administrator and supervisor in the Philippine school system. In this country, there is a rapidly growing recognition that democratic administration and supervision are necessary to the development and operation of a democratic education
Keywords: School management and organization- philippines